An Experimental Investigation on Human Spatial Control Skill Development*. Issue 32 (2016) - Li, Bin; Mettler, Bérénice
Abstract: The advances of modern human-machine systems change the roles of humans and motivate us to promote our understanding of human functions in human-machine systems and their progress through development. This paper illustrates human spatial control skill development through a remote-control flight task, which involves agile system dynamics, multiple control inputs coordination, and long-duration repetitions. The results demonstrate that skill development is a nonlinear process that progresses from purely open-loop control, to the coordination of open-loop control and closed-loop modulations, and finally to the emergence of interaction patterns. The paper also discusses the specificity effect of practice and the transition to generalization through skill development. The techniques developed in this paper ensure the generality of the conclusions across tasks.